2019
DOI: 10.1038/s41598-019-39886-9
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Hybrid Cytokine IL233 Mediates regeneration following Doxorubicin-Induced Nephrotoxic Injury

Abstract: Kidney injury, whether due to ischemic insults or chemotherapeutic agents, is exacerbated by inflammation, whereas Tregs are protective. We recently showed that IL-2 and IL-33, especially as a hybrid cytokine (IL233 - bearing IL-2 and IL-33 activities in one molecule), potentiated Tregs and group 2 innate lymphoid cells (ILC2) to prevent renal injury. Recent studies have indicated a reparative function for Tregs and ILC2. Here, using doxorubicin-induced nephrotoxic renal injury model, we investigated whether I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 67 publications
1
31
0
Order By: Relevance
“…Administration of soluble ST2 (sST2; 100 µg/day, on days 1, 2, and 3 of cisplatin administration) decreased the levels of SCr, acute tubular necrosis, and tubular apoptosis [20]. The dose of IL-33 used in this study was higher than that used in other recent studies [48][49][50][51]. It is not clear if the detrimental effect of exogenous IL-33 observed in this study resulted from the excessive immune response elicited by IL-33.…”
Section: Roles Of Endogenous Il-33 Versus Exogenous Il-33 In Kidney Imentioning
confidence: 62%
See 4 more Smart Citations
“…Administration of soluble ST2 (sST2; 100 µg/day, on days 1, 2, and 3 of cisplatin administration) decreased the levels of SCr, acute tubular necrosis, and tubular apoptosis [20]. The dose of IL-33 used in this study was higher than that used in other recent studies [48][49][50][51]. It is not clear if the detrimental effect of exogenous IL-33 observed in this study resulted from the excessive immune response elicited by IL-33.…”
Section: Roles Of Endogenous Il-33 Versus Exogenous Il-33 In Kidney Imentioning
confidence: 62%
“…Several studies have reported the pathological roles of IL-33 in renal IRI [53], cisplatin-induced AKI [20], and ovalbumin-induced nephrotoxicity models [56]. Additionally, some recent studies have demonstrated that IL-33-mediated immune responses contribute to renal protection in the mouse AKI models [48][49][50][51]. The IL-33/ST2 signaling pathway may function as a double-edged sword and is involved in both the pathological and tissue reparative processes by affecting various cell types at different phases of disease progression [18].…”
Section: Roles Of Il-33-mediated Ilc2 Activation In the Kidneymentioning
confidence: 99%
See 3 more Smart Citations